Evaluation of the relationship between hemodialysis-related glycemic variability and hormonal profiles in patients with type 2 diabetes on hemodialysis: a pilot study - Akinori Hayashi; Kenta Matoba; Yasuhiro Ohata; Naoya Shimizu; Agena Suzuki; Satoe Fujii; Marie Sato; Koji Takano; Masayoshi Shichiri (Renal Replacement Therapy, 2022)
Abstract Background The number of dialysis patients with diabetes is currently increasing in Japan and a similar proportion worldwide. It was suggested that approximately 20% of these patients had hypoglycemia after dialysis session and most of these hypoglycemia were unconscious. Furthermore, it was suggested that glucose variabilities induced by hemodialysis may be related to insulin and insulin-counter hormones, such as glucagon, adrenocorticotropic hormone (ACTH), and cortisol and growth hormone, but conclusive evidence has not still been obtained. Methods We investigated in detail the glucose and hormonal profiles in 7 patients with type 2 diabetes on hemodialysis (all male, HbA1c 6.8 ± 2.1%, glycated albumin 24.7 ± 10.2%). All participants were attached continuous glucose monitoring (iPro2®). Blood glucose level, C-peptide immunoreactivity, plasma glucagon, ACTH, cortisol and growth hormone were measured by 7 points blood tests at before breakfast, after breakfast (predialysis), 2 h and 4 h after starting dialysis, after lunch and before/after dinner on the dialysis day and 6 points at before/after each meal on the non-dialysis day, and these relationship with blood glucose dynamics were examined. The meal contents were set to the indicated energy amount, and the same menu was served daily for breakfast, lunch, and dinner on dialysis and non-dialysis days of this study period. In addition, the start time of lunch on non-dialysis day was the same as the start time of lunch on the dialysis day. Results Serum C-peptide level was significantly increased by taking breakfast and lunch on the hemodialysis day, significantly decreased during hemodialysis, and was significantly lower before and after lunch on the hemodialysis day than on the non-hemodialysis day. Plasma glucagon level significantly decreased during hemodialysis and that before lunch on hemodialysis day was significantly lower than on non-hemodialysis day. ACTH, cortisol, and growth hormone did not show any changes related to hemodialysis. Conclusions It was suggested that C-peptide and glucagon play an important role in hemodialysis-related glycemic variabilities in patients with type 2 diabetic hemodialysis. Trial registration UMIN Clinical Trial Registry (Registration Number UMIN000018707 ). Registered 18 August 2015, https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&language=J&recptno=R000021647 .